Physicochemical Characterization, Storage Stability Behavior, and Intestinal Bioaccessibility of Clove Extract Encapsulated Using Varying Combinations of Gum Arabic and Maltodextrin - Farhad Ahmadi; Hafiz A. R. Suleria; Frank R. Dunshea (Foods)
Clove (Syzygium aromaticum, L.) is a rich source of polyphenols and antioxidants, but its intense flavor, poor solubility, and instability may limit its widespread and efficient use in industrial applications. In a series of laboratory-scale experiments, gum Arabic (GA) and maltodextrin (MD) were used as coating agents in various proportions (ranging from 0MD:100GA to 100MD:0GA) for encapsulation of clove extract using a freeze-drying method. The encapsulates were assessed for the physicochemical properties, storage stability behavior, and intestinal bioaccessibility of phenolics using an in vitro gastrointestinal digestion test. The freeze-dried encapsulates were characterized as having low water activity (<0.3, which is a critical threshold to ensure chemical and microbiological stability), high water solubility (>90%), solid (product) recovery (mean 93.1 ± 1.77%), and encapsulation efficiency (91.4−94.9%). Hygroscopicity increased as the GA:MD proportion increased in the encapsulation formulations. Encapsulation was effective in protecting bioactive components of clove extract during storage at room (up to 40 days) or high temperature (60 °C for 7 days) and minimized the loss of antioxidant activity during storage, as compared to the clove extract in a non-encapsulated form. All encapsulation formulations were characterized by a negative zeta potential (from −22.1 to −29.7 mV) and a polydispersity index ranging from 0.47 to 0.68, classifying the formulations as having a mid-range polydisperse particle size distribution. The FTIR analysis demonstrated that the freeze-drying encapsulation process resulted in no evident chemical interaction between coating and core materials. Intestinal bioaccessibility of total phenolics after the in vitro-simulated gastrointestinal digestion was greater in the encapsulated clove extract compared to the non-encapsulated clove extract. In conclusion, the encapsulation process was effective in protecting the bioactivity of the polyphenol-rich clove extract during storage and improved the phenolic bioaccessibility, potentially supporting the application of the encapsulated clove extract for use in functional food development.